Penguatan Kapasitas Siswa SMK Gelora Jaya Nusantara melalui Pelatihan Soft Skills Tech Leadership sebagai Persiapan Memasuki Dunia Industri - Rena Nainggolan; Rijois I. E Saragih; Eva Julia Gunawati Harianja; Jamaluddin Jamaluddin; Gortap Lumbantoruan; Darwis R. Manalu; Eviyanti Novita Purba; Junika Napitupulu; Marlyna I Hutapea; Resianta Perangin-angin; Rimbun Siringoringo; Roni J. Simamora; Elsya Secilia Margaretha; Marihot Gultom; Henri Yosua Pangihutan; Octania Togatorop; Azelia Sarah Dwi Artha; Nehemia Christian Boy (Universitas Methodist Indonesia, 2025)
The development of industries based on digital technology requires vocational high school (SMK) graduates not only to have technical competencies but also strong soft skills, particularly in technology leadership (tech leadership). Students majoring in Computer and Network Engineering (TKJ) need to be equipped with communication skills, teamwork, problem-solving, and decision-making abilities to be able to adapt and compete in a dynamic industrial world. This community service activity aims to improve the competencies of SMK Gelora Jaya Nusantara students through Soft Skills Tech Leaders training as an effort to prepare them for the challenges of the workforce. The implementation methods include interactive workshops, group discussions, case study simulations, and learning reflections. The results of the activity show an increase in students' understanding of the roles and responsibilities of a tech leader and the importance of soft skills in managing technology projects. Participants showed high enthusiasm and active involvement throughout the training. This activity is expected to serve as a strategic step in supporting the readiness of the younger generation to face digital transformation and the demands of Industry 4.0.